The professional is personal, the personal is professional? Towards re-conceptualising professionalism: a scientific and personal dialogue - Rothe, Antje; del Negro, Gaia; West, Linden (Adult Education Discourses, 2022)
In this paper, two new and one established researcher (from Germany, Italy, and the UK) dialogue about researching professional biographies in education. The authors seek to build on a personal and scientific conversation to illuminate the critical and reflexive epistemological potential of particular perspectives in challenging the constraints of neoliberal discourses in education. The doctoral studies of the new researchers illuminate the limited conceptualisations of professionalism, shaped by dominant discourses pervading higher, adult and early childhood education. The two new authors explore similarities and differences in their work, including research questions, theoretical frameworks, methodologies, empirical data and interpretation. Biographical interviews and co-operative inquiry are used to collect stories about professional identity and ways of knowing. A common finding is that professionalism encompasses deeply personal dimensions in what is a complex conscious and unconscious, cognitive and emotional dynamic. Professionals can feel subjected to external standards and disempowered by constant audit and they must negotiate who they are within these parameters. The exploration of the interplay of past and present spheres of uncertainty fundamentally challenges technocratic and instrumentalist discourses and illuminates the diverse ways of knowing implicated in being a good enough creative and questioning professional. The authors conclude by arguing for a holistic re-conceptualisation of professionalism, as necessarily both personal and professional; and they conceive ‘reflexive irritation’ to be a site of epistemological struggle in this regard. There is also a discussion on related methodological and ethical issues.